Measurement of Friction Coefficient between Glass and Rubik's Beam on the Sloping Field using Rubik Lubricant - Try Adi Sucipto (Journal of Natural Sciences and Mathematics Research, 2019)
This research is based on a rubik game involving the coefficient of friction. Rubik when difficult to rotate then the coefficient of friction is large. Rubik has several lubricants including Maru Lube, Ellips, and Kit Shampoo. This study aims to determine friction coefficient between the inclined plane of glass and rubik beams with lubricating. The beam is launched on an inclined plane and measured travel time. The results of the measurement of the coefficient of friction of the three lubricants namely Maru Lube lubricant has a coefficient of friction value of 0.4586, Ellips lubricant of 0.4375, and shampoo Kit lubricant of 0.4630. Based on these data it can be concluded that Ellips lubricant is the most slippery and more effective lubricant to use.